General Recommendations and Experiences of My Loi CSV Farmers and Ha Tinh Agricultural Staff during ACIS Project from 2015-2018 - Le Thi Tam; Le Dinh Hoa; Le Thi Thao; Duong Minh Tuan (2018)
The poster discusses the general recommendations and experiences of My Loi CSV Farmers and Ha Tinh Agricultural Staff during “Agro-Climate Information Services for women and ethnic minority (ACIS) farmers in Southeast Asia” project from 2015-2018. These include information on crop selection, timing, and management in case of extreme weather events (i.e., drought, hot spell, heavy rain, flooding, storm, and cold spell/ frost. It also contains the recommendations for specific faming systems (e.g., rice; bean or cassava intercropped with peanut-bean and/or maize in rotation; maize intercropped with sweet potato, among others) and the tree suitability with extreme weather events.